2022
DOI: 10.1021/acschemneuro.2c00304
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that GIRK Channels Mediate the DREADD-hM4Di Receptor Activation-Induced Reduction in Membrane Excitability of Striatal Medium Spiny Neurons

Abstract: The hM4Di receptor-based chemogenetic DREADD system has been widely used to suppress neuronal activities, which has contributed substantially to the identification of behavior-associated neuronal circuitries including those in the striatum. One major mechanism by which hM4Di receptor activation suppresses neuronal activity is that the activation reduces membrane excitability, which is thought to be mediated by the opening of GIRK channels. However, previous studies have suggested that GIRK channels are barely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…The hM4Di receptor-based chemogenetic designer receptors exclusively activated by designer drugs (DREADD) system has been widely used to suppress neuronal activity. 34 We conducted experiments to verify the feasibility of this method, and the results are shown in Figure 6B. We found that pre-infecting unaffected axons with hM4Di-DREADD did not affect behavior following intraperitoneal injection of saline.…”
Section: Resultsmentioning
confidence: 91%
“…The hM4Di receptor-based chemogenetic designer receptors exclusively activated by designer drugs (DREADD) system has been widely used to suppress neuronal activity. 34 We conducted experiments to verify the feasibility of this method, and the results are shown in Figure 6B. We found that pre-infecting unaffected axons with hM4Di-DREADD did not affect behavior following intraperitoneal injection of saline.…”
Section: Resultsmentioning
confidence: 91%
“…A possible concern raised by this mechanism of action is whether the neurons expressing DREADDs also express sufficient numbers of GIRK channels. To address this concern, a recent study has shown that neurons in brain areas with low GIRK expression are still able to respond to hM4Di activation via GIRK channels to reduce membrane excitability ( Shan et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, extrasynaptic D2 receptors, such as those in A2A-D2 heteroreceptor complexes, further decrease the firing of striatal-pallidal GABA neurons. The inclusion of GIRK channels in the postsynaptic striatal-pallidal GABA neuron was hypothesized based on experimental evidence in striatal medium spiny neurons (MSNs) (Shan et al, 2022(Shan et al, ). 10.3389/fncel.2024 Frontiers in Cellular Neuroscience 05 frontiersin.org…”
Section: Understanding Volume Transmissionmentioning
confidence: 99%